До питання про поняття та види державних соціальних допомог - Вознюк, Н.; Voznyuk, N. (Східноєвроп. нац. ун-т ім. Лесі Українки, 2014)
У статті обґрунтовано актуальність дослідження теоретичних аспектів державних соціальних допомог, уточнене визначення їх поняття. Запропонована авторська класифікація державних соціальних допомог залежно від страхового ризику та суб’єктного складу. Вказано на окремі недоліки правового регулювання державних соціальних допомог в Україні, внесено загальні пропозиції щодо вдосконалення чинного законодавства. Встановлення ознак державних соціальних допомог, юридичне закріплення їх поняття та класифікації, розміщення переліку всіх видів допомог в єдиному нормативно-правовому акті – Соціальному кодексі України - сприятиме більш повній реалізації громадянами права на соціальний захист.In the article the actuality of the study of the theoretical aspects of state social assistance is defined, definition of the concept is spesified. The author proposed the state social assistance classification depending on the insurance risk and subject composition. In accordance wiht this criterion, the state social assistance is combined into four groups: state social assistance for the birth and upbringing of the child; state social assistance in connection with low income; state social assistance in the event of certain specified events of legislation and assistance to persons with special status. Under these conditions, the lack of a legal act regulating the general principles of public social assistance, would contain a complete list of species, limits public awareness on social protection. This situation, in our opinion, is a barrier to exercise their right to social protection. It is therefore advisable to reform the legal regulation of social assistance. The article stated for certain deficiencies of legal regulation of state social assistance in Ukraine, made general suggestions for improving the current legislation. It is proposed to consolidate legally notion and normative list of state social assistance in a codified legal act that will allow to eliminate discrepancies between separate normative legal acts to unify and simplify the appointment and payment of state social assistance procedure.
Issue of the Determination and Types of State Social Assistance.
Keywords: соціальне забезпечення; державні соціальні допомоги; грошова виплата; прожитковий мінімум; малозабезпеченість; social security; state social assistance; cash payments; cost of living; low income